Investigation into the Effect of Molds in Grasses on Their Content of Low Molecular Mass Thiols - Skládanka, Jiří; Adam, Vojtěch; Zítka, Ondřej; Kryštofová, Olga; Beklová, Miroslava; Kizek, René; Havlíček, Zdeněk; Sláma, Petr; Nawrath, adam (MDPI, 2012)
The aim of this study was to investigate the effect of molds on levels of low molecular mass thiols in grasses. For this purpose, the three grass species Lolium perenne, Festulolium pabulare and Festulolium braunii were cultivated and sampled during four months, from June to September. The same species were also grown under controlled conditions. High-performance liquid chromatography with electrochemical detection was used for quantification of cysteine, reduced (GSH) and oxidized (GSSG) glutathione, and phytochelatins (PC2, PC3, PC4 and PC5). Data were statistically processed and analyzed. Thiols were present in all examined grass species. The effect of fungicide treatments applied under field conditions on the content of the evaluated thiols was shown to be insignificant. Species influenced (p < 0.05) PC3 and GSSG content. F. pabulare, an intergeneric hybrid of drought- and fungi-resistant Festuca arundinacea, was comparable in PC3 content with L. perenne and F. braunii under field conditions. Under controlled conditions, however, F. pabulare had higher (p < 0.05) PC3 content than did L. perenne and F. braunii. Under field conditions, differences between the evaluated species were recorded only in GSSG content, but only sampling in June was significant. F. pabulare had higher (p < 0.05) GSSG content in June than did L. perenne and F. braunii.

The aim of this study was to investigate the effect of molds on levels of low molecular mass thiols in grasses. For this purpose, the three grass species Lolium perenne, Festulolium pabulare and Festulolium braunii were cultivated and sampled during four months, from June to September. The same species were also grown under controlled conditions. High-performance liquid chromatography with electrochemical detection was used for quantification of cysteine, reduced (GSH) and oxidized (GSSG) glutathione, and phytochelatins (PC2, PC3, PC4 and PC5). Data were statistically processed and analyzed. Thiols were present in all examined grass species. The effect of fungicide treatments applied under field conditions on the content of the evaluated thiols was shown to be insignificant. Species influenced (p < 0.05) PC3 and GSSG content. F. pabulare, an intergeneric hybrid of drought- and fungi-resistant Festuca arundinacea, was comparable in PC3 content with L. perenne and F. braunii under field conditions. Under controlled conditions, however, F. pabulare had higher (p < 0.05) PC3 content than did L. perenne and F. braunii. Under field conditions, differences between the evaluated species were recorded only in GSSG content, but only sampling in June was significant. F. pabulare had higher (p < 0.05) GSSG content in June than did L. perenne and F. braunii.
Investigation into the Effect of Molds in Grasses on Their Content of Low Molecular Mass Thiols
Keywords: grass; mold; thiols; glutathione; phytochelatin; grass; mold; thiols; glutathione; phytochelatin